REVIEW AND APPLICATION OF MODERN LABORATORY PROGRAMS IN PHYSICS AND ASTRONOMY FOR STUDENTS: ADVANTAGES AND DISADVANTAGES (Web of Teachers: Inderscience Research, 2024)
This article reviews modern laboratory programs in physics and astronomy used for teaching students. The main advantages, such as interactivity, accessibility and safety, are described, and disadvantages, including limited realism and technical problems, are identified. Examples of popular programs, such as PhET Interactive Simulations, Labster, Stellarium and Celestia are given. The article focuses on the importance of integrating innovative technologies into the educational process to improve the quality of teaching and training of specialists.